Evidence-Based Insurance Development for Nigeria’s Farmers: Briefing paper for Nigerian Federal Ministry of Agriculture and Rural Development (FMARD)-CCAFS Knowledge-Sharing Workshop, London, 27-28 January 2015 - Hellin, Jonathan; Hansen, James W.; Araba D (2015)
Agricultural insurance has been a feature in Nigeria for over two decades. The Federal Government has plans to expand agricultural insurance in the Country as part of several initiatives under the Agricultural Transformation Agenda (ATA). The Government wishes to extend crop insurance to those farmers benefiting from fertilizer subsidies under the Growth Enhancement Support Scheme (GES). The Government also wishes to implement weather index insurance (parametric insurance) in selected parts of the country susceptible droughts and floods. Experiences from index insurance initiatives worldwide provide important lessons for the development of crop index insurance in Nigeria. Experiences from India, Kenya, Rwanda, Ethiopia and Senegal suggest that there is demand for index insurance; that the bundling of insurance with key farm inputs e.g. improved seed and fertilizer, makes the insurance package more attractive to farmers; but that several challenges still to overcome, including data management, basis risk, logistical and client communication. CCAFS could play a role in working with the Federal Government to overcome some of these challenges.